The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/tgis.12997
|View full text |Cite
|
Sign up to set email alerts
|

Solving location‐allocation problems with professional optimization software

Abstract: Location‐allocation modeling has always been regarded as a core part of spatial analysis. A review of the literature, however, reveals that, nevertheless, publications related to facility location disappeared almost completely from geographic journals in the meantime. It can be assumed that one major reason for this development is the limited capability of the location‐allocation modules implemented in GIS packages that prevents this software from being used to solve the increasingly complex real‐world problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 104 publications
(168 reference statements)
0
1
0
Order By: Relevance
“…The spatial optimization of location selection in continuous space has focused on a range of different planning criteria and issues (see Church, 2019; Drezner, 2022; Murray et al, 2020; Plastria, 1995; Wolf, 2022). Hakimi (1964) was among the first to highlight the need for addressing access and coverage but assumed that potential locations were discrete, not continuous, and concluded that addressing both issues was too complicated.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial optimization of location selection in continuous space has focused on a range of different planning criteria and issues (see Church, 2019; Drezner, 2022; Murray et al, 2020; Plastria, 1995; Wolf, 2022). Hakimi (1964) was among the first to highlight the need for addressing access and coverage but assumed that potential locations were discrete, not continuous, and concluded that addressing both issues was too complicated.…”
Section: Introductionmentioning
confidence: 99%